Informal Names in the City (on the Example of the City of Kharkiv) - Удовенко, Лідія (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2019)
The article deals with informal urban citizens in the name of the question. And determine the cause of the main groups of the informal names of urban facilities and reported to the features of the informal name of the city. Listed factors influencing the nomination process of informal urban facilities. The author of the article reports on the future directions of the study of unofficial names in the city.